Empowering EFL Student Writers through a Genre-Based Approach with Critical Pedagogy: Tracing Sociopolitical Consciousness through Freire’s Ten Values and Sociopolitical Consciousness Assessment - Insuwan, Chatuporn; Thongrin, Saneh (วารสารศิลปศาสตร์ มหาวิทยาลัยธรรมศาสตร์, 2025)
Built on our previous research (Insuwan & Thongrin, 2025), which emphasized students’ criticality and argumentative writing skills through a genre-based critical pedagogy approach, this study examines how classroom interactions, as observed through Freire’s Ten Values of Critical Pedagogy, contributed to 32 college students’ sense of empowerment in academic discussions. Data sources included recorded classroom observations interpreted by Freire’s (2005) Ten Values and a sociopolitical consciousness assessment (Baker & Brookins, 2014), analyzed by two raters. A mixed-methods analysis revealed the participants’ highest engagement with Value 5 (teacher-initiated dialogue on real-world issues) and Value 10 (a supportive teacher-student relationship). These findings highlight the teacher’s role as a facilitator fostering co-learning in line with Freire’s concept of dialogue. Other values receiving high ratings included Value 8, emphasizing critical discussions on societal issues, a foundation for sociopolitical consciousness, Value 2, recognizing students’ realities, Value 7, showing mutual respect, and Value 6, encouraging students to challenge societal norms. These findings aligned with qualitative comments from the two raters and the Sociopolitical Consciousness (SPC) Assessment (Baker & Brookins, 2014). The participants expressed highest sociopolitical awareness in Equality and Rights, Collective Action, Responsibility for the Poor, and Sociopolitical Awareness, while Localized Community Efficacy scored the lowest. These findings indicated that the integrative genre-based approach combined with critical pedagogy, as implemented in our previous work, could effectively empower the participants and fostered their sociopolitical consciousness.